The Spectral Returns of The Merchant of Venice in Marina Carr’s Portia Coughlan: "Only his shadow?" - Wald, Christina (Shakespeare bulletin, 2021)
This article discusses Marina Carr’s play Portia Coughlan (1996) as a response to The Merchant of Venice that works against the neglect of Portia in more recent adaptation history. Portia Coughlan places Shakespeare’s female protagonist center stage in a historically updated sequel to The Merchant, which transfers the early modern concern with growing mercantilism and social mobility to the globalized capitalism of the late twentieth century. In Carr’s play, which is itself concerned with ghostly returns, aspects of the long and rich adaptation history of The Merchant spectrally return; it can productively be read alongside specific twentieth-century theatrical productions of The Merchant as well as in relation to Shakespeare’s own mythic, literary, and folktale sources. The intertextual traces of Portia as revenant that inform Shakespeare’s comedy are turned into the central conflict of Carr’s play. Drawing on Freud’s reading of The Merchant of Venice and Judith Butler’s concept of gender melancholia, this article argues that Carr’s third-wave feminist adaptation turns The Merchant’s complex negotiation of social differentiation, pivoting around racialized religion, into a drama of gender/sex differentiation enforced by regionally and nationally inflected kinship structures. In the adaptational network of The Merchant of Venice, Carr’s Portia Coughlan offers a particular approach to the retroactive projection called "original": by reworking Shakespeare’s interest in substance-shadow relationships, it emphasizes the mysterious, menacing, and melancholic aspects of Shakespeare’s Portia figure and elaborates the tragic dimensions of sex/gender differentiation.